THE REPRESENTATIONS OF HOMOPHOBIA IN GAY-THEMED AMERICAN MOVIES 1990s–2010s - Stella Maris Saraswati Mere (Rubikon : Journal of Transnational American Studies, 2017)
The United States is well-known for its acceptance of homosexuality. Nevertheless, homophobia remains a threat that endangers gay communities in the United States. Homophobia is an intriguing phenomenon for American filmmakers. Through gay-themed movies, those filmmakers intend to raise the awareness that homophobia is elusive to eradicate. This study scrutinizes the representations of homophobia in the United States as seen in gay-themed American movies. The study carries out Postnationalist America Studies as the paradigm of the study which encompasses the discussions of numerous phenomena in the United States. Also, the study applies theory of representation by Stuart Hall probing the representations of homophobia in gay-themed American movies of 1990s-2010s. The study uses nine gay-themed American movies of 1990s-2010s as the primary data of the research. The findings of the study show three representations of homophobia in the United States, which encompass religions, gender roles, heteronormativity, masculinity, and HIV/AIDS as the highlighted factors that incite homophobia. By highlighting those major factors of homophobia, the filmmakers come up with two major intentions. The first intention is the movies as means to criticize the society who conforms to strict religious beliefs, traditional gender roles, masculinity, and heteronormativity. The conformity has led the society to commit homophobia, hence making homophobia elusive to eradicate. The second intention is the movies are aimed at encouraging gay communities to keep fighting for their issues and equality.  Keywords: Homosexuality, Homophobia, the United States, Gay-themed American Movies